Outcomes, dosing, and predictors of vedolizumab treatment in children with inflammatory bowel disease (VEDOKIDS): a prospective, multicentre cohort study. (January 2023) - Atia, Ohad; Shavit-Brunschwig, Zivia; Mould, Diane R; Stein, Ronen; Matar, Manar; Aloi, Marina; Ledder, Oren; Focht, Gili; Urlep, Darja; Hyams, Jeffrey; Broide, Efrat; Weiss, Batia; et al.
Summary: Background: Scarce data are available on the use of vedolizumab in children with inflammatory bowel disease (IBD). We aimed to evaluate the safety, effectiveness, and dosing of vedolizumab to induce remission of IBD. Methods: VEDOKIDS was a paediatric, multicentre, prospective cohort study done in 17 centres in six countries. We report the 14-week outcomes as the first analyses of the planned 3-year follow-up of the VEDOKIDS cohort. Children (aged 0–18 years) with IBD who had commenced vedolizumab were followed up at baseline and at 2, 6, and 14 weeks. Children were managed according to local prescribing practices without standardisation of dosing or criteria for escalation, but the study protocol suggested dosing of 177 mg/m 2 body surface area (up to 300 mg maximum). The primary outcome was steroid-free and exclusive enteral nutrition-free remission at 14 weeks, analysed according to the intention-to-treat principle. Serum samples were taken for analysis of drug concentration and faecal calprotectin at baseline, and at 2, 6, and 14 weeks. Adverse events were recorded in real time and classified as severe or non-severe and related or unrelated to vedolizumab. This study is registered with ClinicalTrials.gov, NCT02862132 . Findings: Between May 19, 2016, and April 1, 2022, 142 children (76 [54%] girls and 66 [46%] boys; mean age 13·6 years [SD 3·6]) were enrolled. 65 (46%) children had Crohn's disease, 68 (48%) had ulcerative colitis, and nine (6%) had unclassified IBD (those with unclassified IBD were analysed with the ulcerative colitis group). 32 (42% [95% CI 30–54]) of 77 children with ulcerative colitis and 21 (32% [23–45]) of 65 children with Crohn's disease were in steroid-free and exclusive enteral nutrition-free remission at 14 weeks. Median drug concentrations at week 14 were higher in children with ulcerative colitis than in those with Crohn's disease (11·5 μg/mL [IQR 5·5–18·1] vs 5·9 μg/mL [3·0–12·7]; p=0·006). In children who weighed less than 30 kg, the optimal drug concentration associated with steroid-free and exclusive enteral nutrition-free clinical remission was 7 μg/mL at week 14 (area under the curve 0·69 [95% CI 0·41–0·98]), corresponding to a dose of 200 mg/m 2 body surface area or 10 mg/kg. 32 (23%) of 142 children reported at least one adverse event, the most common were headache (five [4%]), myalgia (four [3%]), and fever (three [2%]). None of the adverse events were classified as severe, and only two (1%) patients discontinued treatment due to adverse events. Interpretation: Vedolizumab showed good safety and effectiveness at inducing remission in children with IBD at 14 weeks, especially those with ulcerative colitis. Vedolizumab should be considered in children when other approved drug interventions for IBD are unsuccessful. In children who weigh less than 30 kg, vedolizumab should be dosed by the child's body surface area (200 mg/m 2 ) or weight (10 mg/kg). Funding: The European Crohn's and Colitis Organization, the European Society for Paediatric Gastroenterology Hepatology and Nutrition, and Takeda.